TEICOPLANIN RESISTANCE IN GRAM-POSITIVE BACTERIAL ISOLATE: AN EMERGING THREAT - CHANDEL, SATISH; SHARMA, PARAG; AKHANI, PRATIK; AGRAWAL, RAMESH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Development of antimicrobial resistance in microorganism isolated from blood stream infection constitutes a major concern about their treatment. Teicoplanin is a glycopeptide antibiotic used in the treatment of infection caused by Gram-positive bacteria. This study was planned to determine Teicoplanin resistance in the Central India and recommend policy changes for prevention of the future resistance to the higher antibiotics. Methods: A total of 1855 septicemia suspected blood samples were studied. The blood culture samples were processed and identified in the microbiology laboratory according to the Clinical and Laboratory Standards Institute guidelines. Antibiotic susceptibility test was done using Kirby B disk diffusion method. Results: About 39.5% of blood culture samples showed positive growth for organism. We observed high teicoplanin resistance (29.5%) among Gram-positive isolates, predominantly (53%) in the Enterococcus species. Conclusion: Teicoplanin resistance has emerged tremendously in the present study. Hence, attention is required about this serious issue otherwise very limited choice of antibiotics will be available for treating infections in the future.